2004
DOI: 10.1023/b:bile.0000013714.88796.5f
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Induced Production of Human Growth Hormone by High Cell Density Cultivation of Recombinant Escherichia Coli

Abstract: The temperature-induced, over-expression of the human growth hormone gene in a recombinant E. coli during high cell density cultivation is reported. Human growth hormone (hGH) production and stability were tested under different heat shock conditions. Cell densities were 25 and 60 g l(-1) in a pH-stat fed-batch mode in defined and complex medium, respectively, and the fermentation time was decreased from 41 to 32 h. hGH was produced at 2 g l(-1) in complex medium. By using glycerol as main carbon source in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 13 publications
0
19
1
2
Order By: Relevance
“…Nevertheless, the activity in aggregates inversely correlates to the temperature [16]. In thermoinducible systems, the IB formation has also been attributed to the increase in recombinant protein synthesis rate and mRNA overexpression [43], recombinant protein amount [42][43][44][45][46], and activation of some heat shock proteins that could favor the disorder in folding reactions [3,42,43,47]. Furthermore, IB formation is favored by shake flask conditions using chemical [13] or thermo-inducible [48] recombinant strains.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the activity in aggregates inversely correlates to the temperature [16]. In thermoinducible systems, the IB formation has also been attributed to the increase in recombinant protein synthesis rate and mRNA overexpression [43], recombinant protein amount [42][43][44][45][46], and activation of some heat shock proteins that could favor the disorder in folding reactions [3,42,43,47]. Furthermore, IB formation is favored by shake flask conditions using chemical [13] or thermo-inducible [48] recombinant strains.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial Strains and Plasmids E. coli JM109 (endA1, gyrA96, thi, hsdR17, supE44, relA1, Δ(lac-proAB), recA1, F′[traD36, proAB + , lacl q , lacZΔM15]) was used as the host strain for pMKAK1-2 [2]. The recombinant plasmid pMKAK1-2 contains a gene encoding the cDNA of porcine muscle ADK under the control of the E. coli tac promoter [2] (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The recombinant plasmid pMKAK1-2 contains a gene encoding the cDNA of porcine muscle ADK under the control of the E. coli tac promoter [2] (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears that the overly high protein expression rate is another reason for the formation of inclusion bodies. It has been confirmed that prokaryotic expression systems are preferred in the production of non-glycosylated r-hGH with biological activity [27,28], and that the r-hGH in inclusion bodies can be easily purified from the culture broth and undergo renaturation to bioactive forms [29]. Therefore, all fed-batch cultures were conducted at 37°C for enhancing the cell growth and the expression of r-hGH.…”
Section: Expression Of R-hgh At Different Temperaturesmentioning
confidence: 98%